SOME CONSIDERATIONS ON THE RIGHT TO HEALTH - ONE OF MAN’S FUNDAMENTAL RIGHTS - Oana ŞARAMET (VALAHIA UNIVERSITY LAW STUDY, 2017)
The right to life is guaranteed to every human being, much like the right to physical and psychological integrity. In order to fully exercise these rights, the human being must truly enjoy good health. As any human has the right to life, he has the right to health and the protection of health. Thus, any human being has the right to a healthy life and the state, much like regional and international organizations, must ensure the necessary background in order for the people to exercise this right. Also, in case of health issues, any person must be ensured the minimum necessary conditions in order to treat any health issues. It may seem counterintuitive, but the right to health was proclaimed on an international level by a document elaborated before the Universal Declaration of Human Rights. However, most people usually struggle to maintain good health, especially in the least developed countries, by pursuing a fight not only to maintain their health but also to protect it. It is essential not only to acknowledge, protect, even guarantee this right by international regulations or even constitutions, as such a fundamental tight allows any human being to fully exercise this right. Thus, creating medical systems and medical insurance systems must allow every human being access to a minimal package of medical services, which are essential and necessary in order to exercise the right to health and the protection of it.
Keywords: : fundamental right; health; protection of health; regulation; equality